2017
DOI: 10.1007/978-3-319-65627-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: Abstract. This collected volume gives a concise account of the most relevant scientific results of the COST Action IS1104 "The EU in the new complex geography of economic systems: models, tools and policy evaluation", a four-year project supported by COST (European Cooperation in Science and Technology). It is divided into three parts reflecting the different perspectives under which complex spatial economic systems have been studied: (i) the Macro perspective looks at the interactions among international or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A direct consequence of this hypothesis is that firms decide actively on their location considering their market needs, the position of other market participants, external factors (e.g., politics), and other aspects. With constant discussions and developments of the underlying theories and approaches (Fingleton, 2007;Martin, 1999), a wide range of methods for empirical analyses has been developed (Commendatore et al, 2018). Two main subjects of research are observed in this context: the evaluation of those factors determining the location of economic activity and the assessment of the impact of locationspecific characteristics on costs and prices.…”
Section: Literature Review and Contributionmentioning
confidence: 99%
“…A direct consequence of this hypothesis is that firms decide actively on their location considering their market needs, the position of other market participants, external factors (e.g., politics), and other aspects. With constant discussions and developments of the underlying theories and approaches (Fingleton, 2007;Martin, 1999), a wide range of methods for empirical analyses has been developed (Commendatore et al, 2018). Two main subjects of research are observed in this context: the evaluation of those factors determining the location of economic activity and the assessment of the impact of locationspecific characteristics on costs and prices.…”
Section: Literature Review and Contributionmentioning
confidence: 99%